2020
DOI: 10.3390/agriculture10050188
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Cash Crop Production on Household Food Security for Smallholder Farmers: A Case of Shamva District, Zimbabwe

Abstract: Zimbabwe has recently experienced a considerable shift towards the production of more cash crops, such as tobacco, at the expense of food crops. Although cash cropping has been associated with increased income, the question is whether the income gained from cash crops would be enough to provide the food needs of farming households. This research was conducted to analyse the impact of cash crops on household food security. A cross-sectional survey consisting of 281 randomly selected smallholder farmers in Shamv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 24 publications
4
21
0
Order By: Relevance
“…The food insecurity drivers carried out in Zambia showed that farming members and off-farm income were significantly associated negatively and positively, respectively, with the prevalence of household food insecurity [33]. The study put having a large household size as positively, and total non-farm income as negatively correlated with food insecurity [39]. In a review of studies regarding food insecurity analysis in Afghanistan, Oskorouchi et al found a positive and significant relationship between flood and food insecurity [40].…”
Section: Introductionmentioning
confidence: 97%
“…The food insecurity drivers carried out in Zambia showed that farming members and off-farm income were significantly associated negatively and positively, respectively, with the prevalence of household food insecurity [33]. The study put having a large household size as positively, and total non-farm income as negatively correlated with food insecurity [39]. In a review of studies regarding food insecurity analysis in Afghanistan, Oskorouchi et al found a positive and significant relationship between flood and food insecurity [40].…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, it remains unclear to what extent and under which conditions can cash crops influence food security [10]. In general, empirical evidence on the relationship between cash cropping and food security remains inconclusive [10,38,42,59]. Some authors posit that cash crops displace food crops [30,44] and undermine food security by rendering households more dependent on market conditions for food [37,75].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, some studies suggest that cash crops rather enhance the food security of farmers by increasing incomes [41,68,73]. The question still remains whether income gains from cash crops would be enough to satisfy the food needs of farming households [59].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where, zi = 1 for high value market zi = 0 for non-high value market xi = the vector of observed covariates for the i th subject Following Rubhara et al (2020), the study used PSM to investigate the impact of participation in a high-value market on cattle production (the number of cattle sold was used as a proxy). Propensity score values are dependent on a vector of observed covariates that are associated with the receipt of treatment.…”
Section: Model Specificationmentioning
confidence: 99%